Konseling Gizi kepada Pengasuh dalam Manajemen Pemenuhan Kebutuhan Nutrisi Anak dengan HIV/AIDS - Baiq Fitria Frisma Lita; Allenidekania Allenidekania (Journal of Telenursing (JOTING), 2021)
This study aims to describe the management of nutritional counseling to caregivers regarding the management of meeting the nutritional needs of children with HIV/AIDS based on the results of several literature searches. The design used in this scientific paper is an integrated literature review. This study indicates that several aspects affect the ability to meet the nutritional needs of children with HIV/AIDS. The nutritional counseling carried out illustrates that the element of food security is still the main thing that affects the ability of the caregiver to help meet the daily nutritional needs of children with HIV/AIDS. Another thing that influences the practice of fulfilling nutrition by caregivers is the level of knowledge, socio-culture, and health workers' role as providers of education related to nutrition. Keywords: Children, HIV/AIDS, Counseling, Nutrition, Caregivers